Day 3 Wed, October 28, 2020 2020
DOI: 10.2118/201365-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic and Numerical Investigation of Trapped Oil Mobilization with Hydrophilic Magnetic Nanoparticles

Abstract: Nanoparticles have great potential to mobilize trapped oil in reservoirs by reducing the oil-water interfacial tension, altering the rock wettability, stabilizing foams and emulsions, and heating the reservoir to decrease the oil viscosity. However, the direct application of magnetic forces on paramagnetic nanoparticles in reservoir engineering applications has not be extensively investigated. We demonstrate the enhanced oil recovery (EOR) potential of hydrophilic magnetic nanoparticles in oil production by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The technology is neutral in relation to the intensity of corrosion, the rate of salt deposition, the development of sulfate-reducing bacteria in oilfield equipment, and also does not affect the preparation process and the quality of commercial oil. (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The technology is neutral in relation to the intensity of corrosion, the rate of salt deposition, the development of sulfate-reducing bacteria in oilfield equipment, and also does not affect the preparation process and the quality of commercial oil. (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Nanotechnology frontiersin.org magnetic field improves oil recovery when the magnetic field direction is along the flow direction. However, Wang et al developed a 3D model based on volume of fluid method and predicted the prohibits the oil recovery when the magnetic field direction is transverse to the flow direction, which is in contrary to their experimental results, hinting the presence of other mechanisms (Wang et al, 2021), (Wang et al, 2020). Magnetic nanoparticles form temporal micro-structures when exposed to external disturbances of either magnetic fields (Robbes et al, 2011), (Tracy and Crawford, 2013) or shears (Ishida et al, 2021), as shown in Figure 15.…”
Section: Figure 14mentioning
confidence: 94%
“…Even when a uniform external magnetic field H is applied, the magnetization M and the magnetic flux density B is non-uniform at the pore scale because of the contrast of magnetic permeabilities of rock, oil, and brine. As a result, the corresponding magnetic-induced pressure is thus non-uniform in the ferrofluid as the flooding fluid (Prodanovic et al, 2010), (Soares et al, 2014;Wang and Prodanovic, 2017;Wang et al, 2020;Wang et al, 2021), as shown in Figure 14. This non-uniform magnetic pressure leads to deformation of the oil-ferrofluid interface and helps the mobilization of the oil droplet in the pore space.…”
Section: General Low-frequency Magnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations